Evaluating Healthcare Teams’ Knowledge about Hospital Triage: A Review of Studies Conducted in Iran - Abiri, Samaneh; Mehramiz, Neema John; Foroughian, Mahdi; Kalani, Navid; Habibzadeh, Seyed Reza; Jelyani, Najmeh Zarei (International Journal of Psychosocial Rehabilitation, 2020)
Background and aim: As a part of the emergency department structure, hospital triage performs by the emergency healthcare team. Scant information exists on healthcare teams’ knowledge about triage. Therefore, this study aimed to review the studies conducted on the healthcare teams’ knowledge about hospital triage in Iran.Materials and methods: This systematic review searched the databases of Sid, Google Scholar, Magiran and Iran Medex to find Farsi articles published on this topic using the keywords of triage and hospital triage. Overall, nine papers were evaluated after the search.Results: The articles assessed in this study were conducted during 2010-2017. Seven papers were of descriptive type while the other two were quasi-experimental. In addition, the studies were performed on nurses, emergency medical personnel, as well as nursing, medical, and emergency medical students. The knowledge level of healthcare teams was unfavorable in five studies, whereas it was favorable and moderate in three and one research, respectively.Conclusion: According to the results of the study, the healthcare teams’ knowledge about triage was unfavorable in most studies. However, triage training increased knowledge about hospital triage in healthcare teams. As such, it is recommended that workshops and retraining courses be held to increase healthcare teams’ knowledge about hospital triage.